Polytetrafluoroethylene versus polypropylene sutures for Essed-Schroeder tunical plication - Horst, Christof van der; Martínez y Portillo, Francisco-José; Melchior, Diethild; Bross, Stephan; Alken, Peter; Jünemann, Klaus-Peter (The journal of urology, 2003)
Purpose: - - Essed-Schroeder plication is an established operative technique to correct congenital and acquired penile deviation. However, a third of all patients complain about discomfort from the suture material used. We prospectively evaluated patient satisfaction and quality of life after modified Essed-Schroeder plication by comparing 2 suture materials. - - Materials and Methods: - - Between 1998 and 2001, 88 patients underwent surgical correction of penile deviation at our hospital. Mean patient age was 40 years (range 18 to 71) and mean followup was 30 months. Preoperatively penile curvature was greater than 20 degrees in all patients. A standardized questionnaire was sent to all patients. A total of 55 patients, including 30 with Peyronie’s disease (PD) and 25 with congenital penile deviation (CPD), were available for evaluation and had complete followup. - - Results: - - In 25 of these patients (12 with PD and 13 with CPD) nonabsorbable polypropylene (PP) sutures were used for plication, whereas in the other 30 (18 with PD and 12 with CPD) nonabsorbable polytetrafluoroethylene (PT) sutures were used. In the PP group 22 of the 25 patients (88%) could notice the sutures (11 with PD and 11 with CPD), 10 had discomfort (6 with PD and 4 with CPD) and 3 had pain during penile erection (2 with PD and 1 with CPD). In the PT group 15 of the 30 patients (50%) could notice the sutures (10 with PD and 5 with CPD), 3 had discomfort (1 with PD and 2 with CPD) and 1 with PD had painful erections. Three patients had recurrent deviation, of whom 2 and 1 underwent plication with PP and PT, respectively. - - Conclusions: - - These results indicate the PT is the more superior suture material with regard to postoperative patient discomfort after Essed-Schroeder correction of penile deviation. Nonabsorbable PT sutures do not impair the efficacy of the modified Essed-Schroeder plication technique and the success rate is not related to the underlying pathological condition.